Prognostic factors in intramedullary ependymomas - Orrego Puelles, Enrique (2021)
Objective: To study the good prognostic factors, overall survival (OS) and progression-free survival (PFS) in a group of patients who underwent an intramedullary ependymoma surgery. Such factors are related to the patient, tumor, type of surgical resection and adjunctive treatment. Materials and methods: A retrospective, analytical and descriptive study conducted in 40 patients who underwent an intramedullary ependymoma surgery between 1985 and 2017 at the Instituto Nacional de Enfermedades Neoplásicas (INEN). The research used IBM SPSS Statistics for Windows 2017. The survival rate was estimated using the Kaplan-Meier product-limit model. The comparison of survival curves was determined by the log-rank test. A probability (p value) less than 0.05 was considered as statistically significant. Results: Out of the 40 patients, 33 were adults and seven were children. The male to female ratio was 1.4:1. The most frequent symptom was motor deficit, which occurred in 97.50 % of the patients. The mean and median of the disease period were 24.90 and 19 months, respectively, with a range of 2 to 108 months. The condition occurred most frequently in the cervical (47.50 %) and lumbar (25 %) areas. Forty percent (40 %) of the patients developed syringomyelia. Concerning their size, 60 % of the tumors covered three to five levels, and 32.50 % were larger than five levels. Thirty percent (30 %), 60 % and 10 % of the patients underwent a total, subtotal and partial resection, respectively. Seventyseven point five zero percent (77.50 %) of the patients had grade II ependymoma, 15 % had grade I and 7.50 % had grade III. Thirty-three (33) patients (82.50 %) received radiotherapy (RTx) and three, chemotherapy (CTx). Overall survival accounted for 240 months. Age, sex, tumor size and disease were not statistically significant predictors of survival. Total resection showed survival rates of 100 %, 90 % and 90 % at 5, 10 and 15 years, respectively, and statistically significant differences in relation to partial and subtotal resections (p < 0.011). There were statistically significant differences in the group of patients who received radiotherapy (p < 0.002). Progression-free survival accounted for 168 months. There were statistically significant differences in the progression-free survival regarding total resection and adjuvant radiotherapy, but no differences in the other variables. A mild to moderate motor deficit improved life prognosis during postoperative and follow-up periods. Conclusions: Several factors affect overall survival and progression-free survival rates, with the most frequent being total resection and radiotherapy, and the least frequent a good preoperative motor function.